Ant colony optimisation for solving university course timetabling problems - Mazlan, Munirah; Makhtar, Mokhairi; Firdaus Khair Ahmad Khairi, Ahmad; Afendee Mohamed, Mohamad; Nordin Abdul Rahman, Mohd (International Journal of Engineering and Technology, 2018)
Course timetabling is one of the most important activities faced by any educational institution. Furthermore, the course timetabling process is time-consuming and tiresome as it needs to be prepared for each regular semester. This paper aims to apply the Ant Colony Optimisation (ACO) method to solve the course timetabling problem. This approach is to optimise the properties of the course requirement and minimise various conflicts for the time slot assignation. This method is based on the life of the ant colony in generating automatic timetabling according to the properties (pheromones) such as time, student, lecturer and room, besides satisfying the constraints. The implementation of this method is to find an effective and better solution for university course timetabling. The result and performance evaluation is used to determine whether it is reliable in providing the feasible timetable.Â Â
Keywords: Ant Colony Optimisation (ACO); Constraints; Course timetabling; Optimisation.